Entrepreneurship Education’s Influence on Learner’s Entrepreneurship Intention in South African Schools - Tshehla, Steven; Chodokufa, Kudakwashe; Costa, King (My University, 2021)
Youth unemployment remains a South African problem and a global concern. Entrepreneurial activity enables people to identify opportunities and start new business ventures helping in addressing Youth unemployment. This study focuses on assessing the influence of entrepreneurship education on the learners’ intention towards entrepreneurship careers in high schools. A quantitative study was conducted consisting of 240 grade 12 learners with entrepreneurship education from the three townships in the City of Tshwane namely Mamelodi, Atteridgeville and Soshanguve. A structured close-ended questionnaire was used to collect data. Data was analysed using descriptive and inferential statistics using SPSS software. Findings have proven a relationship between theoretical education and experiential learning with learners’ intention towards entrepreneurship, with experiential learning significantly influencing the development of entrepreneurship intention in learners. Hence, to improve effectiveness of entrepreneurship education in high school learners, there should be emphasis on experiential learning. Study further indicated that entrepreneurship as a subject has an influence on the choice of entrepreneurship as a career. It is for this reason that learners should interaction with business people globally in order to gain exposure to people who have succeeded by taking entrepreneurship as a career.
Keywords: Entrepreneurship Education; Intention; theoretical education and experiential learning